Kardiochirurgia dorosłychAortic valve remodelling with Urbański’s technique of separate patches – own experience - Bitner, Mirosław; Banyś, Andrzej; Jander, Sławomir; Walczak, Andrzej; Ostrowski, Stanisław; Wojtasik, Leszek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Background: In 2005 Dr Urbanski described modification of the aortic valve remodelling technique in 20 patients. Since July 2006 we have been using his method. Aim: Evaluation of technical aspects, efficacy and usefulness of this technique based on our results. Material and Methods: 17 patients with complicated aortic root pathology were operated on until February 2008, aged 27 to 66 (54±11 on average), 15 with severe aortic insufficiency, 5 with dissection, 11 male (Euroscore 4.65%–59.45%, 12.12±13.13% on average). Valve competence was achieved by restoration of root symmetry with replacement of one or two Valsalva Sinuses (23 sinuses in 17 patients), wedge reduction plasty of some of not excised ones with good quality wall (7 in total), and repair these dissected, which were not removed (10 in total). In this way proper diameter of neo-sino-tubular junction was obtained, stabilized next by supracommissural prosthesis of the ascending aorta. Echocardiography was performed during the operation, before discharge, and every 6 months. In this period 46 patients, including 12 with dissection, required different operative methods. Results: In 15 patients (88%) we achieved a good early result. Two required conversion to AVR (12%). One patient with 4-month-old chronic dissection died on postoperative day 1 from multiorgan failure (mortality rate 5.9%). There was no progress of aortic insufficiency on follow-up so far. Conclusions: This method deals with every component of functional aortic annulus, allows individualized reconstruction of the aortic root, and spares all good quality tissue. Therefore in our experience is suitable for more than 1/4 patients within the entire spectrum of aortic root pathology, including dissection, with efficacy of 88%.